Coal Dust Exposure and Gingivial Lead Line in Coal Miners - Widodo1 , Sahdhina Rismawati1 , Eko Suhartono2 , R. Darmawan Setijanto3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Coal dust contains less than 1% lead (Pb). This dust can enter the body through breathing, mouth and skin. Lead contained in coal dust can react with Sulfur and form gingivial leadline. The study was an observational study with cross-sectional design. The research subjects were coal miners in Sambung Makmur Sub-District, Banjar District, amounting to 100 people. The number of samples was calculated by the Slovin formula and obtained 80 people as samples and determined by simple random sampling technique. The sample obtained then determined the value of the gingivial lead line score as done by Sudibyo. The degree of gingivial lead line is assessed based on the score as follows: 0 = no gingivial lead line; 1 = gingivial lead line found in 1-2 marginal gingival anterior teeth labial surface; 2 = gingivial lead line found at 3-4 marginal gingival anterior teeth labial surface; 3 = gingivial lead line at>4 marginal gingival anterior teeth labial surface. In addition, age, working period (tenure), and smoking habits are the variables measured in this study. The data obtained were analyzed using the chi-square test with a = 5%. The conclusion is the incidence of gingivial leadline of coal miners was related to age, tenure, and smoking habits.